INFLUENCE OF QUALITY OF WORK LIFE, WORK LIFE BALANCE AND EMPLOYEE ENGAGEMENTON PERFORMANCE THROUGH PERSON ORGANIZATION FITEMPLOYEE AT PLANNING AGENCY RESEARCH DEVELOPMENT AND DEVELOPMENT OF TANJUNGPINANG CITY - Sheptya Y.Putri; Indrayani; Muammar Khaddafi; Diana Titik Windayati (RADJA PUBLIKA, 2023)
In this study, researchers used mixed methods research (Qualitative and Quantitative) with the subject being all ASNs in the Research and Development Planning Agency for the City of Tanjungpinang, totaling 120 people. The data collection method used was distributing questionnaires to employees who were the research subjects. The discussion in this chapter is the result of a field study to obtain questionnaire answer data that measures 5 (five) main variables in this study, namely Quality of Work Life, Work Life Balance, Employee Engagement, Performance and Person Organizational Fit. Data analysis with parametric and non-parametric statistics using SEM-PLS (Structural Equation Modeling Partial Least Square) regarding research variables, instrument tests, normality tests, hypothesis testing and discussion of the results of hypothesis testing and path analysis. This study uses path analysis (Path Analysis) to examine the pattern of relationships that reveal the effect of a variable or set of variables on other variables, both direct and indirect effects. Calculation of the path coefficient in this study was assisted by Smart PLS Ver 3.0. To find out the direct and indirect effects between variables, it can be seen from the calculation of the path coefficient and to find out the significance.